Ventrikel Septum Defek (VSD) & Eisenmenger Syndrome - Muhammad Akil (Lembaga Pengembangan Kinerja Dosen, 2026)
Ventricular septal defect (VSD) is a congenital heart defect characterized by a gap in the interventricular septum, with a prevalence of 20–30% of all cases of congenital heart disease. Based on their location, VSD is divided into perimembrane, muscular, and subarterial. This case report discusses a patient who came to the emergency room of Cut Meutia Hospital with good consciousness (GCS E4M6V5) and complained of shortness of breath, cough, nausea, and chest pain spreading to the neck and hands. The anamnesis showed chronic symptoms in the form of coughing up phlegm for two weeks, accompanied by throbbing headaches, dizziness, flatulence, and sleep disturbances. Physical examination showed vital signs of TD 140/90 mmHg, HR 86 x/min, RR 23 x/min, SpO₂ 37%, and temperature 37°C. Supporting examinations in the form of chest X-rays showed cardiomegaly of the pulmonary segment, while ECG showed rhythmic sinuses with LAD axis, T-inverted in AVL, V1, V2, RsR' in V2, positive Cornell criteria, anterolateral myocardial infarction, RBBB, and LVH. Echocardiography shows the presence of a bidirectional shunt with a dominant right-to-left shunt. This case confirms the importance of comprehensive diagnosis through clinical and supporting examinations to determine optimal management in patients with VSD, as well as prevent further complications.